A Comprehensive Study on Electric Vehicles: Operation, Comparison, and Future Prospects - Dr. Jaghannath. K (Educational Administration: Theory and Practice, 2024)
Due to the problems caused by the gasoline engine on the environment and people, the automotive industry has turned to the electrical powered vehicle. This report explains how an electric vehicle works and compares the electric vehicle to the internal combustion engine and hybrid vehicle. The report provides some of the advantages and disadvantages of the electric vehicle. In addition, a brief future view of the technology is given. At a time when the fuel prices are rocketing sky high , the daily running cost of a vehicle and its cost of ownership are hitting the roof and there is a dire need to protect our environment , alternative means of transport are few . Electric vehicle are slow expensive with limited range the solution comes in the form of Electrical vehicle.